2015
DOI: 10.1038/onc.2015.259
|View full text |Cite
|
Sign up to set email alerts
|

PAK5-mediated E47 phosphorylation promotes epithelial–mesenchymal transition and metastasis of colon cancer

Abstract: The p21-activated kinase 5 (PAK5) is overexpressed in advanced cancer and the transcription factor E47 is a direct repressor of E-cadherin and inducer of epithelial-mesenchymal transition (EMT). However, the relationship between PAK5 and E47 has not been explored. In this study, we found that PAK5-mediated E47 phosphorylation promoted EMT in advanced colon cancer. PAK5 interacted with E47 and phosphorylated E47 on Ser39 under hepatocyte growth factor (HGF) stimulation, which decreased cell-cell cohesion, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…PAK5 phosphorylation of BAD on Ser112 inhibits apoptosis (Cotteret et al, 2003; Wang et al, 2010). PAK5 phosphorylation of GATA-1 on Ser161 and Ser187 causes epithelial-to-mesenchymal transition in breast cancer cells, phosphorylation of E47 on Ser39 promotes colon cancer metastasis (Li et al, 2015b; Zhu et al, 2016), and phosphorylation of p120-catenin-Ser288 facilitates cytoskeleton reorganization with implications in cancer cell motility and invasion (Wong et al, 2012).…”
Section: Pak5/7 Biologymentioning
confidence: 99%
“…PAK5 phosphorylation of BAD on Ser112 inhibits apoptosis (Cotteret et al, 2003; Wang et al, 2010). PAK5 phosphorylation of GATA-1 on Ser161 and Ser187 causes epithelial-to-mesenchymal transition in breast cancer cells, phosphorylation of E47 on Ser39 promotes colon cancer metastasis (Li et al, 2015b; Zhu et al, 2016), and phosphorylation of p120-catenin-Ser288 facilitates cytoskeleton reorganization with implications in cancer cell motility and invasion (Wong et al, 2012).…”
Section: Pak5/7 Biologymentioning
confidence: 99%
“…Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival . Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers . Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5–early growth response protein 1 (Egr1)–matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers. [7][8][9][10][11] Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5-early growth response protein 1 (Egr1)-matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion. 12 PAK5-directed GATA1 phosphorylation has been reported to induce epithelialmesenchymal transition in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…There were 32 types of TFBSs within the first intron fragment, including the enhancers, i.e., CCAAT/enhancer binding protein beta (CEBPB), CCAAT/enhancer binding protein alpha (CEBP), cAMP activated protein (CAP), GATA binding elements (GATA1), LIM-only protein 2 (LMO2COM), myeloid zinc finger 1 (MZF1), simian-virus-40-protein-1 (SP1), basic helix–loop–helix transcription factors (USF), the repressor, acute myeloid leukemia-1 (AML1), and the enhancers or repressor GRE [17,31]. There were also some elements with unclear functions, i.e., AP1, replication initiator 1 (AP4), AP1FJ, c-Ets-1 (CETS1P54), c-Rel (CREL), caudal type homeobox 1 (CDXA), DELTAEF1, cyclin E/E2F (E2F), E47, GATA3, GATA2, hepatocyte nuclear factor 3β (HNF3β), ikappa B kinase-like 2 (IK2), c-Myb (MYB), MYOD, cardiac-specific homeobox protein (NKX25), OCT1, P53, sex-determining region Y (SRY), STAT, TATA, and TST1 [32,33,34,35,36] (Table S1). The 5′-distal region of +55/+372 in the cGH contained a cluster of twenty TFBSs and highly conserved near-consensus TFBSs (score = 1.000) for the transcriptional factor, which was acute myeloid leukemia-1 (AML1).…”
Section: Resultsmentioning
confidence: 99%